جهود علماء التفسير في حركة النقد الأدبي واللغوي في القرن الثالث الهجري: Efforts of scholars of interpretation in the movement of literary and linguistic criticism in the third century AH - Hafez, Hussein Lafta (SIBAWAYH Arabic Language and Education, 2020)
The observer of the critical movement in the second century of Hijra notices that until the end of the second century AH, that criticism remained an innate criticism based on taste and emotion with literary influence. This critical effort combined grammar and rhetorical appreciation that was associated with looking at the Qur’anic text, and the evidence needed for that from the words and poems of the Arabs. In addition to that, criticism remained a marginal work for those critics, most of whom were linguists who were preoccupied with narrating poetry and purifying it from the parable, and strange explanations. This study chose a great scholar who Belongs to the Kufic school. This scientist is Abu al-Abbas Ahmad ibn Yahya, nicknamed (the Kufic Fox), one of the linguists and grammar figures in the third century AH. The study deals with the critical efforts of this scholar in the field of literary and linguistic criticism. The al-Kufi fox realized the importance of linguistic and literary criticism and its close relationship with the integrity and understanding of poetry. Therefore, he paid special attention to it and occupied a large portion of his books, including (Majlis al-Thawq, the explanation of the eloquent, the rules of poetry, the explanation of the divan of al-Khansa, and the explanation of Diwan Asha).